2022
DOI: 10.3390/molecules27082565
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Investigation of Novel CHCA-Derived Matrices for Matrix-Assisted Laser Desorption/Ionization Mass Spectrometric Analysis of Lipids

Abstract: A significant area of study and upgrading for increasing sensitivity and general performances of matrix-assisted laser-desorption ionization (MALDI) mass spectrometry (MS) is related to matrix design. Several efforts have been made to address the challenge of low-mass-region interference-free for metabolomics analysis and specifically for lipidomics. To this aim, rationally designed matrices as 4-chloro-α-cyanocinnamic acid (ClCCA) were introduced and reported to provide enhanced analytical performances. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This may also be considered an advantage because some impurities can be suppressed at optimum conditions. Although there were [ 86 ] (and still are [ 74 ]) many studies to rationally design superior matrix compounds, many of these matrices did not fulfill the expectations. Thus, it has to be admitted that the finding of powerful MALDI matrices is normally an empirical task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also be considered an advantage because some impurities can be suppressed at optimum conditions. Although there were [ 86 ] (and still are [ 74 ]) many studies to rationally design superior matrix compounds, many of these matrices did not fulfill the expectations. Thus, it has to be admitted that the finding of powerful MALDI matrices is normally an empirical task.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was recently shown that CHCA could be converted into more effective matrix compounds [ 74 ]: cyano-naphthyl acrylic acid (CNAA) was particularly useful for phospholipid analysis in general, while cyano nitrophenyl dienoic acid (CNDA) favored the positive ion detection of neutral lipids such as DAG and TAG. Acidic PLs such as PI, PS, PA, and CL (and with slight reservations also PE) are detected with poor sensitivities as positive ions but are readily detected as negative ions.…”
Section: Which Matrix Is Most Suitable For Individual Lipid Classes?mentioning
confidence: 99%
“…Traditional methods for analyzing these fatty molecules in algae have faced some limitations, such as the occurrence of matrix-related background or in-source decay effects by commonly used matrices like 2,5-dihydroxybenzoic acid (DHB) and α-cyano-4-hydroxycinnamic acid (CHCA), hindering proper identification. Significant progress has been made in the analysis of low-molecular-weight (LMW) molecules such as lipids, and other matrices [ 23 , 24 ] with better detection performances have been proposed. For instance, working in the negative ion mode provides simplified spectra and improves sensitivity for several analytes including fatty acids (FAs), lipids, and glycans as deprotonated molecules [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in metabolomics has increased the number of techniques available to characterize clinically relevant small molecules in biological tissues, such as human milk. Currently, high-throughput MS-based analysis of human milk includes nuclear magnetic resonance (NMR) and mass spectrometry (MS) [40]. The metabolomics signature and profile of early human milk (colostrum) has been identified via NMR [41 ▪▪ ] to understand the impact of extreme fetal growth condition on the nutritional value of the milk [41 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%